Optimization of regeneration and Agrobacteriummediated transformation of immature cotyledons of chickpea (Cicer arietinum L.) - Tripathi, L.; Singh, A.K.; Singh, S.; Singh, R.; Chaudhary, S.; Sanyal, I.; Amla, D. (Springer, 2013)
Immature cotyledons collected at different time intervals from four genotypes of chickpea (C 235, BG 256, P 362 and P 372) were cultured adaxially on Murashige and Skoog (MS) medium supplemented with 6-benzyladenine, thidiazuron, kinetin, zeatin and dimethylallylaminopurine (2-iP), either alone or in combination with indole-3-acetic acid (IAA) or a-napthoxyacetic acid (a-NOA) for dedifferentiation and regeneration of adventitious shoots. Morphogenesis was achievedwith explants cultured adaxially onMSmedium with 13.68 lM zeatin, 24.6 lM 2-iP, 0.29 lM IAA and 0.27 lM a-NOA. Explants prepared from pods of 21 days after pollination, responded favourably to plant growth regulator treatment in shoot differentiation.Histological studies of the regenerating explants, revealed the initiation of meristematic activity in the sub-epidermal region during the onset of morphogenesis,which can be correlated with elevated activity of cytokinin oxidase-dehydrogenase, for cytokinin metabolism. The regenerated shoots were efficiently rooted in MS medium supplemented with 2.46 lM indole-3-butyric acid and acclimatized under culture room and glasshouse conditions for normal plant development leading to 76–80 % survival of the rooted plantlets. The immature cotyledon explants were used for Agrobacterium-mediated transformation with critical manipulation of cultural conditions like age of explant, O.D. of Agrobacterium suspension, concentration of acetosyringone, duration of sonication and co-cultivation for successful genetic transformation and expression of the reporter gene uidA (GUS). Integration of transgene was confirmed by molecular analysis. Transformation frequency up to 2.08 % was achieved in chickpea, suggesting the feasibility of using immature cotyledon explants for Agrobacterium-mediated transformation.